Photodynamic therapy for cancer - Shrikant B. Mali; Sachinkumar Dahivelkar (Oral Oncology Reports)
Cancer is clearly one of the most complicated and life-threatening diseases, with increased morbidity and an extraordinarily high death rate, posing a significant danger to human health as well as a significant economic burden on society as a whole. Surgical intervention, chemotherapy, and radiation are among traditional cancer treatment methods. However, the outcomes of these therapies are often disappointing and are frequently linked with serious adverse effects. A increasing corpus of research has revealed that photodynamic therapy (PDT) is an essential treatment technique in cancer and has recently become a hot issue.